Determination of Formaldehyde in Seafood and Food Products at Somdet Market, Kalasin Province - Suwanaruang, Theeranat (Challenging Issues on Environment and Earth Science Vol. 1, 2021)
Formaldehyde or formalin is profoundly harmful that is assimilated agreeably. The object of this exploration was to examine formalin that sullied in fish and solidified meat. The technique was to choose tests at Kalasin Province. The examples were mackerel, fresh squid, solidified chicken, Saba fish, Shishamo fish, Jelly fish, Cockle, Clams, Squid, shrimp, White shrimp and Dolly fish, individually. The techniques were to examine formaldehyde with titration and formalin test kit. Titration technique utilized formic corrosive by abundance of iodine in soluble arrangement. Formalin test unit of Ministry of Public Health issued Act No.151 (B.E.2536) was to test formalin debased food. The results discovered formaldehyde in mackerel, fresh squid, solidified chicken, Saba fish, Shishamo fish, jellyfish, cockle, shellfishes, squid, shrimp, white shrimp and cart fish in three duplicated were 288 mg/L, 228 mg/L, 293 mg/L, 77 mg/L, 282 mg/L, 180 mg/L, 120 mg/L, 48 mg/L, 229 mg/L, 294 mg/L, 295 mg/L and 293 mg/L, individually. Formalin test unit was to establish all examples were contaminated with formalin. In addition, the stature formalin defiled in white shrimp, the second were shrimp and cart fish, the third was solidified chicken, the fourth was mackerel, the fifth was Shishamo fish, the 6th was squid, the seventh was fresh squid, the eighth was jellyfish, the ninth was cockle, the 10th was Saba fish and the latter was shellfish. The World Health Organization arranged formaldehyde was cancer-causing to people, circumspectly that there was a fair evidence for exacting depression malignancy in people.